Low Frequency Ultrasound With Injection of NMO-IgG and Complement Produces Lesions Different From Experimental Autoimmune Encephalomyelitis Mice - Xiang, Weiwei; Xie, Chong; Luo, Jiaying; Zhang, Wei; Zhao, Xinxin; Yang, Hong; Cai, Yu; Ding, Jie; Wang, Yishu; Hao, Yong; Zhang, Ying; Guan, Yangtai (Frontiers in Immunology, 2021)
Neuromyelitis optica spectrum disorder (NMOSD), a relapsing autoimmune disease of the central nervous system, mainly targets the optic nerve and spinal cord. To date, all attempts at the establishment of NMOSD animal models have been based on neuromyelitis optica immunoglobulin G antibody (NMO-IgG) and mimic the disease in part. To solve this problem, we developed a rodent model by opening the blood-brain barrier (BBB) with low frequency ultrasound, followed by injection of NMO-IgG from NMOSD patients and complement to mice suffering pre-existing neuroinflammation produced by experimental autoimmune encephalomyelitis (EAE). In this study, we showed that ultrasound with NMO-IgG and complement caused marked inflammation and demyelination of both spinal cords and optic nerves compared to blank control group, as well as glial fibrillary acidic protein (GFAP) and aquaporin-4 (AQP4) loss of spinal cords and optic nerves compared to EAE mice and EAE mice with only BBB opening. In addition, magnetic resonance imaging (MRI) revealed optic neuritis with spinal cord lesions. We further demonstrated eye segregation defects in the dorsal lateral geniculate nucleus (dLGN) of these NMOSD mice.